2017
DOI: 10.1161/jaha.117.005498
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Stable Patients With Acute Myocardial Infarction and Coronary Artery Bypass Surgery Within 48 Hours: A Single‐Center, Retrospective Experience

Abstract: BackgroundThe optimal timing of coronary artery bypass grafting (CABG) in clinically stable patients with acute myocardial infarction who are unsuitable for percutaneous coronary intervention is unclear. We report our experience with early CABG in these patients.Methods and ResultsBetween January 2001 and May 2015, 766 patients with ST‐segment–elevation myocardial infarction (STEMI, n=305) or non‐STEMI (NSTEMI, n=461) not including cardiogenic shock underwent CABG within 48 hours at our department. STEMI patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
2
14
0
1
Order By: Relevance
“…In agreement with previous studies of ACS and MI patients [ 9 , 15 ], we found in-hospital mortality to be significantly higher when CABG was performed for patients with MI (8.6%) compared to patients with stable CAD (1.6%). This mortality rate is well in line with previous findings of 2.7–21.6% early mortality after CABG in MI patients [ 7 , 15 ]. Increased mortality of MI patients is associated with higher risk of both procedural (e.g.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with previous studies of ACS and MI patients [ 9 , 15 ], we found in-hospital mortality to be significantly higher when CABG was performed for patients with MI (8.6%) compared to patients with stable CAD (1.6%). This mortality rate is well in line with previous findings of 2.7–21.6% early mortality after CABG in MI patients [ 7 , 15 ]. Increased mortality of MI patients is associated with higher risk of both procedural (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Increased mortality of MI patients is associated with higher risk of both procedural (e.g. early bypass dysfunction) and MI related complications [7,15], reflected also to a longer hospitalization period after surgery found in our data. Optimal timing of CABG after MI for maximal benefitrisk gain is unclear [15,16].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In this setting, the optimal timing of CABG has been a matter of debate for decades. More recent data suggest that immediate surgery is equally safe and possibly associated with improved outcomes compared to delaying surgery for some days after the acute event [2,3]. If immediate CABG is the method chosen for myocardial revascularization, the procedure is usually carried out using a heart-lung machine [4].…”
Section: Introductionmentioning
confidence: 99%